Analysis of improved pulsating heat pipe designs for hot spot applications. (1st November 2022) - Schwarz, Florian; Messmer, Pascal; Lodermeyer, Alexander; Danov, Vladimir; Fleßner, Christian; Becker, Stefan; Hellinger, Rolf
Highlights: The flower-shaped pulsating heat pipe design can handle higher heat fluxes compared to the state-of-the-art design The thermal resistance decreases due to continuous phase change processes in the evaporation chamber The fluid oscillation is driven by the phase change in the evaporation chamber Convective heat transfer is negligible in horizontal position Graphical abstract: Abstract: Pulsating heat pipes (PHPs) are increasingly used for the thermal management of hot spots. A major goal in the design process of PHPs is the handling of high heat fluxes and, thus, improved thermal resistance. The thermal resistance can be reduced by increasing the latent or convective heat transfer. Two design approaches with that goal are presented in this study: a flower-shaped PHP design to increase the latent heat transfer and a star-shaped PHP design to increase the convective heat transfer. We compare the proposed designs to a state-of-the-art, meander-shaped PHP design. Thereby, we quantify the thermal performance and the flow pattern of the different PHP designs. The copper PHPs were filled with acetone and tested horizontally and vertically. The filling ratios varied from 0 % to 90 % and the heat inputs increased from 50 W to 200 W. Our results illustrate that the flower-shaped PHP design reduces the thermal resistance by 7 % in horizontal and 12 % in vertical position. We found a strong interrelation between flow pattern and heat transfer in PHPs. Our study shows that phase change plays a key role for the thermal resistance. Based on that, we provide design criteria to optimize the thermal capabilities of PHPs with a special focus on hot spots.